Topographic Evaluation of Inflammatory Periapical Lesions in the First Molar’s Region Using CBCT - Maryam Kazemipoor; Fatemeh Foroughipour; Yaser Safi (International Journal of Dentistry)
Conclusion: Given the limitations of the present study, regarding the extension of the PA lesion in the first molar region, the bone structure of the maxilla and mandible follows a precise and delicate pattern. In this regard, future studies in different communities and races should be designed to address this issue in different communities. In addition, CBCT is a reliable imaging method to evaluate the extension of the PA lesion both morphologically and morphometrically.